Maternal and Neonatal Prognostic Factors for Cardiorespiratory Events in Healthy Term Neonates During Early Skin-to-Skin Contact - Rodríguez-López, Jesús; De la Cruz Bértolo, Javier; García-Lara, Nadia Raquela; Asla Elorriaga, Izaskun; Román Echevarría, Lourdes; Vento, Máximo; Parra-Llorca, Anna; Cabañas, Fernando; Lozano, Pedro; García-Algar, Óscar; Martín-Ancel, Ana; Copons Fernández, Cristina; et al. (Frontiers in Pediatrics, 2022)
Background: During early skin-to-skin contact (ESSC), alterations in peripheral oxygen saturation (SpO2) and heart rate (HR) have been frequently observed. Objectives: This study aimed to determine the incidence of cardiorespiratory events (CREs) during ESSC in healthy term newborns (HTNs) and estimate the association of maternal and neonatal prognostic factors with the risk of CREs. Methods: A pooled analysis of the cohort from a clinical trial involving healthy mother–child dyads during ESSC was performed. Pulse oximetry was employed to continuously monitor SpO2 and HR within 2 h after birth. The individual and combined prognostic relevance of the demographic and clinical characteristics of dyads for the occurrence of a CRE (SpO2 < 91% or HR < 111 beats per minute (bpm) or > 180 bpm) was analyzed through logistic regression models. Results: Of the 254 children assessed, 169 (66.5%; 95% confidence interval [95% CI], 60.5%–72.5%) had at least one CRE. The characteristics that increased the risk of CRE were maternal age ≥ 35 years (odds ratio [OR], 2.21; 95% CI, 1.19–4.09), primiparity (1.96; 1.03–3.72), gestational body mass index (BMI) > 25 kg/m2 (1.92; 1.05–3.53), and birth time between 09:00 pm and 08:59 am (2.47; 1.02–5.97). Conclusions: CREs were more frequent in HTNs born during nighttime and in HTNs born to first-time mothers, mothers ≥ 35 years, and mothers with a gestational BMI > 25 kg/m2. These predictor variables can be determined during childbirth. Identification of neonates at higher risk of developing CREs would allow for closer surveillance during ESSC.